THE IMPACT OF SOCIAL MEDIA ON INTERPERSONAL COMMUNICATION IN THE DIGITAL AGE: https://doi.org/10.5281/zenodo.15480079 - Tadjidinova , Shahzoda; Shomurodova , Sevara; Shabidinova , Zera (Journal of International science networks, 2025)
This article explores the impact of social media on interpersonal communication in the 21st century. While platforms like Facebook, Instagram, and Twitter have enhanced global connectivity and made it easier to maintain long-distance relationships, they have also introduced new challenges. These include reduced face-to-face interactions, superficial relationships, and increased misunderstandings due to lack of non-verbal cues. The study analyzes both positive and negative effects, drawing on recent research, surveys, and expert opinions. It concludes that although social media has transformed communication by making it faster and more convenient, it has also weakened the depth and quality of human connections in many cases. Balanced usage and awareness of its effects are essential for maintaining healthy interpersonal relationships.